Mesearch and the Performing Body - Edward, Mark (Springer International Publishing, 2018)
This book is an anthology of Mark Edward's creative practice-led projects. It transmits and communicates his research through varied artistic means, primarily contemporary dance, immersive art installation, drag performance, and photography. Through the innovative practice of 'mesearch', in which the author is both theoriser and theorised, this study delivers a personal, creative narration, combining reflections and emotions in relation to self and performance. Instead of being an attempt to undervalue or challenge the accepted notions of style within academic research, it promotes a freedom of expression which allows greater fluidity between the researcher, the performer, and the writer.